Incision and Drainage with Daily Irrigation for the Treatment of Auricular Pseudocyst - Abdel Tawab, Hazem M.; Tabook, Salim M. Sloma (International Archives of Otorhinolaryngology, 2019)
Introduction Pseudocyst of the pinna is a rare condition that occurs when fluid accumulates in the intercartilagenous space of the auricle. The main goal when treating this condition is to keep acceptable cosmetic results with no recurrence rate.Objective To demonstrate the superior impact of incision and drainage of auricular pseudocysts with the insertion of a catheter drain and daily irrigation as the treatment of this condition.Methods A total of 42 patients with auricular pseudocysts were enrolled in the present study in the period between May 2011 and May 2017. All of the patients were treated with incision and drainage with compression. The average follow-up time reached ∼ 6 months in all of the cases.Results All of the patients had satisfactory cosmetic results with no recurrence and no complications.Conclusion Among the different methods of surgical treatment of pseudocyst of the pinna, incision and drainage with daily irrigation is a significantly efficient method both for the eradication of auricular pseudocysts and for good cosmetic results.
Keywords: pseudocyst; pinna; incision